2019
DOI: 10.1111/bju.14708
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care use amongst patients with bladder cancer

Abstract: ObjectivesTo describe the rate and determinants of palliative care use amongst Medicare beneficiaries with bladder cancer and encourage a national dialogue on improving coordinated urological, oncological, and palliative care in patients with genitourinary malignancies. Patients and methodsUsing Surveillance, Epidemiology, and End Results-Medicare data, we identified patients diagnosed with muscle-invasive bladder cancer (MIBC) between 2008 and 2013. Our primary outcome was receipt of palliative care, defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
2
29
1
Order By: Relevance
“…26,27 Independent predictors of PC referral revealed potential groups where PC services were underutilized. The lower PC referral utilization in younger patients, male, Hispanics, and lower income patient has been reported in the past 25,28 and requires measures to improve PC referral in these subgroups.…”
Section: Discussionmentioning
confidence: 91%
“…26,27 Independent predictors of PC referral revealed potential groups where PC services were underutilized. The lower PC referral utilization in younger patients, male, Hispanics, and lower income patient has been reported in the past 25,28 and requires measures to improve PC referral in these subgroups.…”
Section: Discussionmentioning
confidence: 91%
“…Palliative care for BC is a still highly uncharacterized issue, with no precise guidelines and indications. American Society of Clinical Oncology recommends early palliative care for patients affected by advanced malignancies, late-stage disease, distant metastasis or life expectancy of 624 months [8, 18]. Hugar et al recently reported, though, that only 4% with patients affected by advanced BC or advanced comorbidities actually undergo palliative treatments among Medicare beneficiaries [8].…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care has been widely described for other malignancies, but we still lack precise guidelines about palliation in BC patients [8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…So far, no targeted therapy is recommended to treat advanced and/or metastatic BC and palliative cystectomy is performed. The prognosis in metastatic BC is generally extremely poor …”
Section: Introductionmentioning
confidence: 99%